Schröpfkopf, Spritze und „stumme Schwester“: „hybride Objekte“ und „Grenzobjekte“ zwischen Pflege und Medizin - Nolte, Karen (Virus, 2021)
The paper aims to show how an object-centred approach to the history of nursing can help toprovide a new perspective on the historical development of the professionalisation of nursingand its demarcation from both the medical profession and non-professional care. Nursing practicesand the material objects closely related to them are analysed in their historical context.We analyse in particular such objects that were used not only by professional nurses but alsoin home care by family members or caregivers and doctors.Indeed, the investigation of the objects and the practices linked to them enables us to showthat professional nursing distinguished itself from non-professional care not necessarily throughspecific nursing objects but through the use of them. Furthermore, professional nurses alwaystook on tasks that belonged to the physicians’ domain without receiving clear instructions asto their authority. While nurses were trained more thoroughly than doctors in handling theseobjects, the practices were both legally and in practice defined as doctors’ tasks.
Gesehen am 23.06.2021